The Irish Soccer Split - Moore, Cormac (Book collections on Project MUSE., 2016)
The Irish Football Association (IFA) was founded in Belfast in 1880. It was the governing body for soccer for the whole of the island of Ireland. Soccer in Ireland was united for over forty years. It was, though, an uneasy alliance. Many in the south believed that the governing body was heavily biased towards Ulster. Most internationals were played in Belfast, most players selected were from the North-East. With the country moving politically towards partition, soccer in Ireland was arguably affected more by the political environment than any other sport. As tensions rose between unionist and nationalist communities, soccer, with strong support bases in both communities, became embroiled in the conflict, playing host to many ugly sectarian incidents. Divisions in the sport reached a climax after the First World War, culminating in the split of 1921 when Leinster seceded from the IFA and formed the Football Association of Ireland (FAI). Making use of extensive primary sources from the IFA, FAI, the English FA and the Leinster Football Association as well as contemporary newspaper sources, The Irish Soccer Split details the events and causes that led to the split in soccer in Ireland. It compares soccer to other sports that remained or became united after partition. The Irish Soccer Split recounts the early years of the FAI and its attempts to gain international recognition. Many efforts were made to heal the division throughout the 1920s and the early 1930s. Efforts were renewed during the Troubles in the 1970s and 1980s to bring about an all-Ireland international team. Some came very close, all ultimately failed.